Geography, space and education in the qur'anic story of moses: A hermeneutical perspective - Safa Alrumayh; Nahid Ayad; Abraheem Alriteemi; Mohieddin Masoud; Mowafg Masuwd; Sami Barkah; Naser Ali Abdulghani; Husna Nashihin (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study explores the role of spatiality in the Qur’anic narrative of Prophet Moses, examining six central locations, Egypt, the river, the palace, Midian, the sea, and Mount Ṭur as transformative stages in the prophetic journey.  Drawing upon classical Qur’anic exegesis and Gadamerian hermeneutics, the research employs a textual-analytical approach to explore how each place functions not merely as a geographical site but as a locus of divine pedagogy and existential formation. The study addresses a gap in Qur’anic studies and educational philosophy by highlighting how spatial interpretation reveals the pedagogical dimensions of prophetic experience and the construction of spiritual identity. Through this lens, the paper contributes to developing a Qur’anic philosophy of sacred space and deepens understanding of divine education in the Qur’anic worldview.